2020
DOI: 10.3389/fpls.2020.571025
|View full text |Cite
|
Sign up to set email alerts
|

Halotropism: Phytohormonal Aspects and Potential Applications

Abstract: Halotropism is a sodium specific tropic movement of roots in order to obtain the optimal salt concentration for proper growth and development. Numerous results suggest that halotropic events are under the control and regulation of complex plant hormone pathway. This minireview collects some recent evidences about sodium sensing during halotropism and the hormonal regulation of halotropic responses in glycophytes. The precise hormonal mechanisms by which halophytes plant roots perceive salt stress and translate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 116 publications
(148 reference statements)
0
9
0
Order By: Relevance
“…Crosstalk interaction with other phytohormones, as well as signaling network are very complex. On the other hand, CKs and auxins can have antagonistic effect at low to medium concentration, and only at higher concentration they have adjunctive effect [ 24 , 50 ]. With respect to gibberellins, little effect has in this halophyte, so the effect of each treatment may be genotype-dependent [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crosstalk interaction with other phytohormones, as well as signaling network are very complex. On the other hand, CKs and auxins can have antagonistic effect at low to medium concentration, and only at higher concentration they have adjunctive effect [ 24 , 50 ]. With respect to gibberellins, little effect has in this halophyte, so the effect of each treatment may be genotype-dependent [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…They also are related to abiotic stress tolerance, and regulate the root: shoot ratio, control stomatal resistance, regulate antioxidant enzymes, delay leaf senescence and act as signal molecules [ 21 ]. Auxins regulate cell elongation, vascular tissue development and apical dominance [ 24 ]. Cytokinins control cell division, chloroplast biogenesis, leaf senescence, shoot differentiation, anthocyanin production and photomorphogenic development [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…A Genome-Wide Association Study (GWAS) into natural variation of halotropism within Arabidopsis identified AtDOB1 and AtCHX13 as additional players in the response ( Deolu-Ajayi et al, 2019 ). Both genes are upregulated under salt stress, and both appear to be involved in Na + /K + homeostasis, suggesting that internal ion homeostasis is likely a key factor underlying the halotropism response ( Galvan-Ampudia et al, 2013 ; Pierik and Testerink, 2014 ; Szepesi, 2020 ). Interestingly, several salt-tolerant, halophyte species such as Brassica indica and Limonium bicolor , show positive halotropism in heterogenous mild saline soils ( Shelef et al, 2010 ; Leng et al, 2019 ).…”
Section: Tropisms and Root Branchingmentioning
confidence: 99%
“…Halotropism is a newly discovered salt avoidance tropism, which allows plant to runaway from salinity by bending. Halotropism can assist plant to remodel root system architecture (RSA) to survive under salt condition (Szepesi, 2020).…”
Section: Lncrna2-fl As a Regulator Of Salt Tolerance In Fl478mentioning
confidence: 99%